Astragalin and rutin restore gut microbiota dysbiosis, alleviate obesity and insulin resistance in high-fat diet-fed C57BL/6J mice - Muni Swamy Ganjayi; Karunakaran Reddy Sankaran; Balaji Meriga; Ruchika Bhatia; Shikha Sharma; Kanthi Kiran Kondepudi (Food Science and Human Wellness)
In the present study we investigated the impact of the combination of astragalin and rutin (CAR) on restoring gut-microbial dysbiosis and obesity and obesity related disorders. Randomized male C57BL/6J mice were experimentally divided into 5 groups and fed either a normal diet or a high-fat diet (HFD) for 16 weeks. Compared to vehicle treated group (HFD group), CAR could substantially improve selected gut microbiota abundance (Akkermansia, Lactobacillus, Bifidobacteria, Roseburia, Prevotella), reversed the Firmicutes/Bacteroidetes proportions, and inhibited the growth of Escherichia coli, Salmonella, and Klebsiella in obese mice. In addition, CAR-treated mice showed significantly increased total short-chain fatty acid production, reduced body weight gain, organs’ weights, serum lipid profile (except HDL) and insulin resistance. The mRNA expressions of CCAAT/enhancer binding protein-α (C/EBP-α), sterol regulatory element-binding protein-1c (SREBP-1c), peroxisome proliferator-activated receptor-γ (PPAR-γ), acetyl-CoA carboxylase (ACC), adipocyte protein 2 (aP2), and fatty acid synthase (FAS) were downregulated (P < 0.05) and the protein expression of PPAR-γ was downregulated while adenosine 5’ monophosphate-activated protein kinase (AMPK) was phosphorylated in CAR-treated HFD-fed mice compared to the HFD control group. Interestingly, CAR-treated HFD-fed mice showed significantly improved tissue architecture in the liver and fatty tissues. In conclusion, the findings suggest that CAR/Moringa oleifera may be beneficial in the treatment of insulin resistance and obesity disorders.